Formation of the mechanism of the control system at the industrial enterprise - Khodyrieva, O. O. (Wydawca "Interdruk", Poland, Warszawa, 2021)
The article outlines some aspects of the formation of a comprehensive controlling system at an industrial enterprise, which is particularly relevant in an unstable environment. The works of Ukrainian and foreign scientists who studied the implementation of controlling at an industrial enterprise are analyzed. The principles of management at development of system of controlling of the industrial enterprises are analyzed and generalized. The variants of the structure of the controlling controlling service at the enterprise are specified and their combination is offered. The process of development and implementation of the controlling system is described. A model of the algorithm for implementing the controlling system at an industrial enterprise has been developed, in which a new stage is proposed: "motivation of innovative activity".
Keywords: controlling; management system; factors of development; economic efficiency; motivation of innovative activity